2016
DOI: 10.1021/acs.langmuir.5b03884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short Chain Poly(ethylene glycol)s on the Hydration Structure and Dynamics around Human Serum Albumin

Abstract: We report the changes in the hydration dynamics around a globular protein, human serum albumin (HSA), in the presence of two short chain crowding agents, namely poly(ethylene glycol)s (PEG 200 and 400). The change in the network water structure is investigated using FTIR spectroscopy in the far-infrared (FIR) frequency range. Site specific changes are obtained by time-resolved fluorescence spectroscopic technique using the intrinsic fluorophore tryptophan (Trp214) of HSA. The collective hydration dynamics of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 57 publications
3
33
0
Order By: Relevance
“…Similar dn rdfs plots were found for the three folded proteins, supporting previous claims by other authors 21 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 pure water at the same temperature), as clearly seen in the first peak (increased) and second peak (decreased) of dn rdf (Figure 1a). A similar effect of attracting water to the protein surface is evident in PEG, supporting previous spectroscopy-derived claims on the ability of PEG to modify the hydration pattern of proteins 25 (see Figure 1a). Finally, it is worth noting that no dramatic differences are found when dn rdfs of folded and unfolded proteins (Figure 1a and b) are compared (note that Figure 1b shows average dn rdf obtained by the entire ensemble derived from the 10 independent trajectories), which supports the idea that, at least from a static point of view, the static picture of hydration around folded and unfolded proteins might not be so different 9,20 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar dn rdfs plots were found for the three folded proteins, supporting previous claims by other authors 21 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 pure water at the same temperature), as clearly seen in the first peak (increased) and second peak (decreased) of dn rdf (Figure 1a). A similar effect of attracting water to the protein surface is evident in PEG, supporting previous spectroscopy-derived claims on the ability of PEG to modify the hydration pattern of proteins 25 (see Figure 1a). Finally, it is worth noting that no dramatic differences are found when dn rdfs of folded and unfolded proteins (Figure 1a and b) are compared (note that Figure 1b shows average dn rdf obtained by the entire ensemble derived from the 10 independent trajectories), which supports the idea that, at least from a static point of view, the static picture of hydration around folded and unfolded proteins might not be so different 9,20 .…”
Section: Resultssupporting
confidence: 86%
“…It is generally accepted that perturbation of the protein by the presence of cosolvents induces certain changes in the structure and dynamics of waters around proteins. For example, it has been suggested 20,[23][24][25] that inert crowding leads to a reduction in the dynamics of water around the protein, mimicking perhaps the situation found in the cellular cytoplasm 20 .…”
Section: Introductionmentioning
confidence: 98%
“…In previouss tudies, we concluded that monovalents alts [53] acted as water-structure breakers, whereas as tructure-making trend was more evident in otherwise naive or protein-stabilizing polymers. [54] We measured the THz-frequency-dependent parameters of different alcohol/water mixtures ( Figure S2). Figure 2a depicts the absorption coefficient measured at 1THz for all three binarym ixtures.…”
Section: Ttds Measurementsmentioning
confidence: 99%
“…And as shown in Figure S7 in the Supporting Information, the size of the NPs incubated in pH 7.4 PBS (10 × 10 −3 m , 0.14 m NaCl) with 10% bovine serum albumin (BSA) would be increased and remained stable with prolongation of incubation time. This result was attributed to that the hydrophilic PEG corona could prevent a large number of protein adsorption of NPs, and the NPs could still be gathered in tumor tissue via enhanced permeability and retention effect due to the size of NPs was below 200 nm . Thus, this system held a potential for drug delivery.…”
Section: Resultsmentioning
confidence: 99%